Salaf Islamic Boarding School Education Curriculum In The Modern Era - Sri Minarti; Farida Isroani (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Results from this search 1) Done Include a curriculum Boarding school predecessor In the 2013 curricula, the local content consists of the internal curriculum, the joint curriculum, and the external methodology, collecting method boarding school The predecessor between learning styles boarding school predecessor and thetechniques learn to talk It uses heritage books for learning 2) Ar Rosyid Islamic Boarding School advances boarding school curriculum, combines techniques modern learning and traditional methods of the salaf boarding school and the get up teachere religious action evaluation questions to Advances Boarding school Curriculum Independently without government help. In this search a type of field research is used with a descriptive model or feature of the qualitative. Used data collection method note: 1). The observation 2) The interview. 3) The documents to be collected from Ar Rosyid. And the style data analysis use served analyzing data at Miles and Huberman Three ways, reduce data, data presentation, and conclusion